PENINGKATAN PEMAHAMAN HUKUM PERLINDUNGAN KONSUMEN DI MASA PANDEMI COVID-19 - Zainal Arifin; Emi Puasa Handayani (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2020)
This activity is “Socialization and Increasing Comprehension of Consumer Protection Law during Covid Pandemic in Dandangan Village, Kediri City”. This program is carried out by universities, especially the Law Faculty of Kadiri Islamic University, to carry out the Tri Dharma of Higher Education, community service to build mutually beneficial relationships. This community service program is run by Higher Education in collaboration with Dandangan Village, Kota, Kediri City. The participants are 17 peoples from Dandangan village, consisting of religious leaders (Toga), community leaders (Tomas), village activists, youth organizations, PKK ladies, and recitation groups. The results of this activity resulted in the following recommendations and evaluations: from the discussion, presentation and questionnaire, we know that the majoritypeoples from Dandangandoesn’t know and understand the meaning of consumer protecting from law perspective.